Dynamic Hydrogels Based on Double Imine Connections and Application for Delivery of Fluorouracil - Zhang, Yan; Pham, Chi-Yen; Yu, Rui; Petit, Eddy; Li, Suming; Barboiu, Mihail (Frontiers in Chemistry, 2020)
Dynamic hydrogels have been prepared by cross-linking of O-carboxymethyl chitosan (O-CMCS) with reversibly connected imino-PEGylated dynamers. The double imine chitosan/dynamer and dynamer bonds and were used to provide tighter structures and adaptive drug release behaviors of the hydrogels. The structural and physical properties of the resulted hydrogels were examined, showing good thermal stability and higher swelling behaviours (up to 3000%). When hydrogels with various composition ratios were further applied for delivery of anti-cancer drug fluorouracil (5-FU), high drug encapsulation rates were recorded, up to 97%. The release profile of 5-FU showed fast rate at the beginning, followed by slow increase to the maximum amount within 12 h, demonstrating potential materials for efficient drug delivery.